Sub-nanosecond tryptophan radical deprotonation mediated by a protein-bound water cluster in class II DNA photolyases. Issue 5 (19th December 2017) - Müller, Pavel; Ignatz, Elisabeth; Kiontke, Stephan; Brettel, Klaus; Essen, Lars-Oliver
Abstract : Light activation of class II DNA photolyases is enhanced by a unique cluster of protein-bound water molecules. Abstract : Class II DNA photolyases are flavoenzymes occurring in both prokaryotes and eukaryotes including higher plants and animals. Despite considerable structural deviations from the well-studied class I DNA photolyases, they share the main biological function, namely light-driven repair of the most common UV-induced lesions in DNA, the cyclobutane pyrimidine dimers (CPDs). For DNA repair activity, photolyases require the fully reduced flavin adenine dinucleotide cofactor, FADH −, which can be obtained from oxidized or semi-reduced FAD by a process called photoactivation. Using transient absorption spectroscopy, we have examined the initial electron and proton transfer reactions leading to photoactivation of the class II DNA photolyase from Methanosarcina mazei . Upon photoexcitation, FAD is reduced via a distinct (class II-specific) chain of three tryptophans, giving rise to an FAD˙ − TrpH˙ + radical pair. The distal Trp388 H˙ + deprotonates to Trp388 ˙ in 350 ps, i.e., by three orders of magnitude faster than TrpH˙ + in aqueous solution or in any previously studied photolyase. We identified a class II-specific cluster of protein-bound water molecules ideally positioned to serve as the primary proton acceptor. The high rate of Trp388 H˙ + deprotonation counters futile radical pair recombination and ensures efficient photoactivation.